Workplace innovation and the role of public policy: evaluating the impact of the Finnish Workplace Development Programme: limits and possibilities - Payne, J (ESRC Centre on Skills, Knowledge and Organisational Performance (SKOPE), 2004)
Academics from a variety of disciplines have recently begun to consider the role that public policy might play in encouraging the development of new and better forms of work organisation aimed at expanding employees' opportunities to exercise skill, discretion and autonomy. The paper explores these questions through an examination of the Finnish Workplace Development Programme, often regarded as a form of public policy intervention, par excellence, explicitly aimed at improving work organisation. Drawing upon interviews with policy makers, employer organisations, trade unions and academics involved with the programme, together with two case studies of development projects in the Finnish municipal sector, it considers how successful the programme has been in its attempt to develop better forms of work organisation that improve both productivity and the quality of working life (QWL). The paper concludes that even in a country which might be regarded as having many of the institutional and political conditions conducive to workplace innovation, there remain definite limits to how far such programmes can help to deliver the 'better job'.